Pengaruh Kualitas Produk Terhadap Minat Beli Konsumen Pada Home Industri Pia Deisy Desa Kapitu Kecamatan Amurang Barat - Karundeng, Nikita; Kalangi, Johny A. F.; Walangitan, Olivia Ch. F. (Sam Ratulangi University, 2019)
This study aims to determine whether Product Quality has an effect on Consumer BuyingInterest. Speaking with quality and buying interest is certainly very tied to marketing. Theessence of marketing according to Daryanto (2011)